Integrated process production and extraction of the fibrinolytic protease from Bacillus sp. UFPEDA 485 - Sales, Amanda Emmanuelle (2013)
Fibrinolytic proteases are enzymes that degrade fibrin; these enzymes are a promising alternative for thrombolytic therapy, and microorganisms produce them. The aim of this study was to evaluate the optimum conditions for the integrated production and purification of fibrinolytic protease from Bacillus sp. UFPEDA 485. Extractive fermentation was carried out in a culture medium containing soybean flour and by adding polyethylene glycol (PEG) and Na2SO4 according to a 23 experimental design. In all assays, the enzyme preferentially partitioned to the bottom phase (K < 1), with an optimum activity of 835 U ml−1 in the bottom phase (salt-rich phase). The best conditions for extractive fermentation were obtained with 18 % PEG 8000 and 13 % Na2SO4. Characterization showed that it is a metalloprotease, as a strong inhibition—residual activity of 3.13 %—occurred in the presence of ethylenediaminetetraacetic acid. It was also observed that enzymatic activity was stimulated in the presence of ions: CaCl2 (440 %), MgCl2 (440 %), FeSO4 (268 %), and KCl (268 %). The obtained results indicate that the use of a low-cost substrate and the integration of fermentation with an aqueous two-phase system extraction may be an interesting alternative for the production of fibrinolytic protease.